Implicações econômicas dos custos de descontratação - Dias, Adriano Batista; Moldau, Juan Hersztajn (Estudos Econômicos (São Paulo), 1992)
This article is concerned with the economic implications of the introduction and increase of lay off costs. This study starts with the analysis of the effect of incomplete information with respect to employment decisions in a stationary economy. Next, as an application of Schumpeter's economic development theory, business cycles and growth are incorporated into the analysis. In addition, the effect of lay off costs on market organization is also brought into this study. The paper concludes that increases in lay off costs tend to inhibit new enrollments consequently, there is a negative effect on employment during the upswing of the business cycle. During deep recessions one can expect an increase in the number of bankruptcies. On the other hand, compensation payments that increase with the period of employment have the effect of stimulating the maintenance of workers employed for a relatively longer period of time.